Bladder metastasis from primary breast cancer: a case report - Kimiyasu Yoneyama; Motohito Nakagawa; Asuka Hara (Surgical Case Reports, 2018)
Abstract Background Breast cancer frequently metastasizes to the bone, lung, and liver. However, metastasis to the bladder is uncommon. Bladder metastasis due to direct infiltration from peripheral organs, such as the colon and rectum, prostate, and cervix, occurs more frequently than metastasis from distant organs, such as the breast. Case presentation We report a case of bladder metastasis identified during treatment for recurrent breast cancer. Fifteen years after her initial surgery, a known breast cancer patient complained of a left lower abdominal pain, anuria, and body swelling. Computed tomography imaging revealed an irregular thickening of the left bladder wall, left hydronephrosis, and hydroureter. A bladder metastasis from breast cancer was diagnosed based on a histological examination of a cystoscopic biopsy specimen. She is currently receiving chemotherapy with eribulin mesylate. Conclusions Routine screening of the lower urinary tract is not necessary for all patients, but women with a history of breast cancer presenting with urinary symptoms should undergo a thorough examination of the urinary tract.